Toward Education 3.0: Pedagogical Affordances and Implications of Social Software and the Semantic Web. (December 2015) - Allison, Mark; Kendrick, Lynn Marie
Abstract : This chapter explores the implications of the new educational paradigm from a technical standpoint and proposes a constructivist‐aware approach to best leverage its significance.